Case Study: Student Perception about Philosophy of Education and Pedagogy in Teacher-Training - Morales, Hernán (2019)
This study took place in Chile at the Universidad Católica de la Santísima Concepción Faculty of Education. The objective of the study was to gain insight about the perception of Education Majors regarding a Philosophy of Education course. The methodology involved a descriptive, qualitative design presented within a case study based on in-depth interviews. The response through which the authors were able to build a narrative detailing perception and the different variables associated with the objective.  Responses were categorized and analyzed using Nvivo 11 software. The most significant results reveal that students are not motivated to take Philosophy of Education or any other type of philosophy course. Yet, they do demonstrate that the study of philosophy is an important part of the Education Major curriculum. More educational resources must be offered, such as additional teaching strategies to help Education Majors further develop their reflexive skills and a renewed didactic approach towards the study of philosophy.